The Galaxy distribution of pulsars - Andreasyan, R. R.; Paronyan, G. M.; Sukiasyan, A. G.
We investigated the distribution of pulsars in our Galaxy. Special attention was paid to Galaxy distribution of millisecond pulsars. We study also the difference of physical properties of millisecond and normal pulsars as well as the differences in physical properties of millisecond pulsars in Globular clusters and these objects in the Galaxy field.
Keywords: Astrophysics